A randomized controlled trial comparing tacrolimus versus hydrocortisone for the treatment of atopic dermatitis in children: new perspectives on interferon gamma-induced protein and growth-related oncogene-α - Binsaleh, Ammena Y.; Bahaa, Mostafa M.; Elmasry, Thanaa A.; Elberri, Eman I.; Kotkata, Fedaa A.; El-Khateeb, Eman; Kamal, Marwa; El-samongy, Marwa Ahmed; Hamouda, Amir O.; Alghamdi, Amira M.; Alrubia, Sarah; Salahuddin, Muhammed M.; et al. (Frontiers in Medicine, 2024)
Introduction: Atopic dermatitis (AD) is a type of chronic inflammatory disorder that affects children. Aim: To investigate whether hydrocortisone or tacrolimus could be more effective for treating AD in children. Patients and Methods: This clinical randomized investigation included 100 children with AD who met the eligibility criteria. AD patients were recruited from Tanta University's Dermatology Department and divided into two groups (n=50)., For four months, group 1 (the hydrocortisone group) received topical hydrocortisone cream. Group 2 received topical tacrolimus for four months. A dermatologist evaluated the patients at the start and four months after the treatment had been initiated to measure serum concentrations of neutrophil chemoattractant growth-related oncogene-α (GRO-α), interferon gamma induced protein 10 (IP-10), tumor necrosis factor alpha (TNF-α), vascular adhesion molecule 1 (VCAM-1), intercellular adhesion molecule 1 (ICAM-1). All patients were examined using the modified Eczema Area and Severity Index (mEASI) score Results: Tacrolimus group showed a significant reduction in serum levels of all measured biomarkers (p < 0.05) when compared to its baseline and when compared to the hydrocortisone group. Both groups displayed a significant decline in mEASI score in comparison with their baseline values (p < 0.05).In children with AD, tacrolimus reduces inflammatory biomarkers better than hydrocortisone, suggesting its potential as a more effective treatment option Trial registration identifier: NCT05607901